Buenos Aires Across the Arts : Five and One Theses on Modernity, 1921-1939 - Kefala, Eleni (Book collections on Project MUSE., 2022)
"Kefala looks at the interaction between modernity and modernism in literature, photography, film, and painting during the interwar period. She analyzes works by Jorge Luis Borges, Oliverio Girondo, Jose Ferreyra, Xul Solar, Roberto Arlt, and Horacio Coppola, with a focus on the city of Buenos Aires as a playground of modernity. This was a period of profound change and heightened cultural activity in Argentina. By 1920, Buenos Aires was Latin America's largest and most cosmopolitan center due to massive immigration from Europe. This had drastic effects on the city's socioeconomic and cultural topography and raised political, ideological, and aesthetic issues that shaped the modernist landscape. Artists responded to these changes with conflicting depictions of urban space. Kefala understands these conflicts themselves as a cognitive map of modernity's new realities in the city and in understandings of the city"--